Communicating with non-scientific audiences - Le Borgne, Ewen (CGIAR Collaborative Platform on Gender Research, 2017)
Presented by Ewen Le Borgne (KIT), as part of the Capacity Development Workshop hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 7-8 December 2017